Dinamisasi Sastra Papua Sebuah Kajian Fenomenologis - Esther Rita Embram (Balai Bahasa Provinsi Papua, 2019)
Papua literature is like Kartenz mountain peaks of Jayawijaya, which stood with strong but so cold because the eternal snow. The position of literature in Papua so alive and together with the Papuan’s identity that putting the culture or customs as the dignity of their lives. So far, the material of literature that developed in Papua has not been much to raise the issue of locality. Papua has counter laden with issues of national and state life dynamisism. Therefore, there needs to be dynamic literary of Papua. Dinamisation literary form in Papua will be discussed in this paper. The goal as well as stimulate the process of literary appreciation of the splendor to the issue of locality in Papua, this paper also wanted to inspire observer and literary enthusiasts in Papua so that more developing literature on the deepening of Papua, with bringing forward local policies (local wisdom) of land in Papua, by increasing the capacity of people living in Papua mental spiritual education. This paper can also be used as reference material efforts to reduce the disharmonisation life of nation and state in Papua.